Positive solutions for systems of m‐point nonlinear boundary value problems - Henderson, Johnny; Ntouyas, Sotiris K.; Purnaras, Ioannis K. (Mathematical Modelling and Analysis, 2008)
Positive solutions (u(t), v(t)) are sought for the nonlocal (m‐point) nonlinear system of boundary value problems, u” + λa(t)f(v) = 0, v” + λb(t)g(u) = 0, for 0 < t < 1, and satisfying, u(0) = 0, u(1) = . An application of a Guo‐Krasnosel'skii fixed point theorem yields sufficient values of λ for which such positive solutions exist.First Published Online: 14 Oct 2010